Parp3 assists muscle function and skeletal muscle differentiation by selectively adjusting H3K27me3 enrichment - Zuleyha Yildirim; Aurélia Noll; Kathline Martin-Hernandez; Jean-Christophe Amé; Najat Hanini; Nadia Messaddeq; Isabelle Robert; Bernardo Reina San Martin; Gunn Hildrestrand; Magnar Bjoras; Françoise Dantzer (iScience)
Summary: Poly(ADP-ribose) polymerase 3 (Parp3) is known for its role in DNA repair, mitotic division, and cancer aggressiveness. Still, its physiological roles have yet to be defined. Here, we combined in vivo studies using Parp3-deficient mice with in cellulo studies to explore the involvement of Parp3 in skeletal muscle function and muscle differentiation. We show that Parp3 contributes to skeletal muscle integrity and promotes myogenic differentiation. Mechanistically, we show that Parp3 promotes the enrichment of the repressive histone mark H3K27me3 onto a panel of selected genes. For some genes, Parp3 also helps the binding of Ezh2, the histone methyltransferase that catalyzes H3K27me3. Moreover, Parp3 ADP-ribosylates Ezh2 in vitro. Altogether, these findings unveil Parp3 as a driver of efficient murine skeletal myogenesis in vitro and muscle function in young adults, and highlight an epigenetic control of gene expression.